Safety profile of drugs for advanced melanoma: A report based on 2008–2018 US Food and Drug Administration Data. Issue 7 (29th December 2020) - Casarotto, Emilie; Noize, Pernelle; Létinier, Louis; Salvo, Francesco; Pham‐Ledard, Anne; Molimard, Mathieu
Abstract : We describe the safety profiles of all drug classes used for the treatment of advanced melanoma from the US Food and Drug Administration Adverse Event Reporting System over 2008–2018. Adverse reactions reported in 25 900 pharmacovigilance cases are described for chemotherapies, immunomodulators, targeted therapies and immunotherapies. There was a sharp increase in the number of cases over time, with peaks associated with the launch of new treatments. The adverse reactions diversified over time; notably, skin (alopecias, dermatitis) and retinal disorders were frequently associated with targeted therapies and endocrine disorders (hypothalamus, thyroid and adrenal dysfunctions) with immunotherapies. Less well‐known reactions were also detected, such as neuropsychiatric disorders with targeted therapies and gastrointestinal ulcers, pneumothorax and pleural effusions with immunotherapies. The findings highlight the need for various health professionals (including medical specialists or trained nurses) to enhance management of complications. Abstract :